Glucagon Stimulation Testing in Assessing for Adult Growth Hormone Deficiency: Current Status and Future Perspectives. (7th July 2011) - Yuen, Kevin C. J.
Abstract : Growth hormone deficiency (GHD) is a well-recognized clinical syndrome in adults. However, due to the high frequency of normal serum IGF-I levels in hypopituitary adults with GHD, it is now widely accepted that despite normal levels of total IGF-I, adults clinically suspected with GHD within the appropriate clinical setting must undergo GH provocative testing to confirm its diagnosis. Although the insulin tolerance test (ITT) is labor intensive, contraindicated in the elderly and in adults with seizure disorders and ischemic heart disease, can be unpleasant for the patient, and is potentially hazardous, this test remains the gold standard test for the biochemical demonstration of GHD in adults. In contrast, with the unavailability of the GHRH and arginine test as the alternative test to the ITT in the United States since 2008, the glucagon stimulation test (GST) has since been increasingly used in the United States because of its availability, reproducibility, safety, lack of influence by gender and hypothalamic cause of GHD, and relatively few contraindications. In this paper, we discuss our recommendations in performing this test, the potential drawbacks in conducting and caveats in interpreting this test, and its future perspectives.